2011
DOI: 10.1021/ol201510u
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Carbocyclic Ring of Indoles Using Ruthenium-Catalyzed Ring-Closing Olefin Metathesis

Abstract: The selective synthesis of substituted indoles was achieved by the ring-closing olefin metathesis (RCM)/elimination sequence or the RCM/tautomerization sequence of functionalized pyrrole precursors. The RCM/elimination sequence was also applied to double ring closure to yield a substituted carbazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Several natural marine products, such as lamellarin O,3 are also pyrrole derivatives. α‐Formylpyrroles are one of the most important five‐membered heterocyclic synthons4 which are used in the preparation of many bioactive compounds including some very important linked polycyclic systems4b (such as the well‐known porphyrin compounds4d,5), fused‐ring compounds,4c,6 and highly‐functional pyrrole derivatives 4a,7. The Vilsmeier–Haack reaction is a widely used method for the synthesis of α‐formylpyrroles 7a,8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several natural marine products, such as lamellarin O,3 are also pyrrole derivatives. α‐Formylpyrroles are one of the most important five‐membered heterocyclic synthons4 which are used in the preparation of many bioactive compounds including some very important linked polycyclic systems4b (such as the well‐known porphyrin compounds4d,5), fused‐ring compounds,4c,6 and highly‐functional pyrrole derivatives 4a,7. The Vilsmeier–Haack reaction is a widely used method for the synthesis of α‐formylpyrroles 7a,8.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the Reimer–Tiemann reaction is also a powerful method for the transformation 9. In addition, oxidation of α‐methyl4d,5a,10 or α‐hydroxymethyl4b,c,5a groups of pyrroles and reduction of an α‐ester group into the aldehyde group via a multi‐step process5c have also been developed to produce α‐formylated pyrroles. However, these strategies often require pre‐preparation of α‐functionalized pyrroles, which often needs additional reaction steps, thus affects the efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshida, Yanagisawa and co-workers have shown that RCM of homoallylic alcohols 40 using G2 generates bicycles 41, which undergo facile acid-promoted elimination to the target indoles (e.g. 42a/b) (Scheme 15a) [58]. The methodology enables access to a wide range of substitution patterns and tolerates N-benzyl and N-sulfonyl protecting groups.…”
Section: Synthesis Of Heteroaromatic Compounds By Alkene and Enyne Mementioning
confidence: 99%
“…Terebic acid, (I), belongs to the -lactone family (fivemembered cyclic esters). Lactones are generally formed by an intramolecular dehydration reaction (cyclocondensation) of hydroxy acid or by an intermolecular dehydration followed by a cyclization involving an alcohol and a carboxylic acid (Yoshida et al, 2011;Eckert et al, 2011).…”
Section: Commentmentioning
confidence: 99%